'A mere historian': Patrick Collinson and the Study of Literature. Issue 342 (October 2015) - Kewes, Paulina
Abstract: Patrick Collinson experienced a 'cultural' or more specifically a 'literary' turn in mid‐career (the early 1980s) which had a profound effect on how he 'did' history. He rarely wrote about overtly 'literary' texts, but he helped to shape the area in which historians and literary scholars could have fruitful dialogue (sixteenth‐century histories and sermons, for example). This essay explores three aspects of this story. First, it examines when, where, how and with whom he came to experience a new and transformative relationship with English literature and its scholars. Second, it scrutinizes the precise forms of that relationship. Third, it considers which of his publications have most influenced English studies and why others, arguably no less important, have been relatively neglected. It finds him at once passionate and strangely diffident, deeply hostile to the New Historicism, for example, but never willing to define his own position against those of whom he was so wary. Despite this, the essay seeks to demonstrate how deeply influential his empirical studies have been in a multi‐disciplinary context.